Implementasi Kebijakan Penyediaan Air Bersih di Kabupaten Badung - Sudiatmika, I Wayan Adi; Trisnawati, Ayu Kade (Bali Membangun Bali: Jurnal Bappeda Litbang, 2025)
Purpose: The fulfillment of clean water needs is a complex problem and requires comprehensive analysis. This study aims to analyze the implementation of clean water supply policies in Badung Regency to identify the strengths, weaknesses, opportunities, and threats. Research methods: This research uses a qualitative methodology with a SWOT analysis approach through data collection carried out by interview and documentation study methods. Results and discussion: The Badung Regency Government together with Perumda Air Minum Tirta Mangutama have implemented several policies to improve clean water supply. However, there are still several obstacles, such as limited raw water source capacity, rapid population growth so that service coverage does not increase significantly. The SWOT analysis results show that to meet the clean water needs in Badung Regency, the Weaknesses-Opportunities strategy is used with strategic policies in the form of developing and increasing the availability of raw water through the support of the central government and the Bali Provincial Government so as to increase the coverage of clean water services through developing alternative financing schemes, such as cooperation with the private sector, financial institutions, and the community. Implication: Efforts to improve the performance of clean water services in Badung Regency require a comprehensive strategy to optimize strengths and opportunities, as well as minimize weaknesses and threats in the implementation of clean water supply policies.